Performance and Thermal Efficiency Analysis of A Household-Scale Waste Incinerator without External Fuel - Nurjaya, Nurjaya; Reson Wibowo,; Nur Rohmat; Muhamad Cahyadi (UIR PRESS, 2026)
Household waste accumulation has become a significant environmental issue in urban areas. This study evaluates the thermal performance and mass-reduction efficiency of a household-scale waste incinerator prototype operating without external fossil fuel under natural-draft airflow. The combustion chamber was fabricated from a cylindrical steel drum equipped with primary air inlets. Mixed household waste (initial mass 5 kg; moisture content 28%) was tested. Temperature was measured using a K-type thermocouple positioned at the chamber centre. The maximum recorded temperature reached 100°C within 40 minutes. Mass reduction reached 25%, calculated based on initial and final mass measurements. The estimated thermal efficiency was 7.1%, determined using a simplified energy balance approach. The results indicate that the prototype operates under low-temperature thermal degradation conditions rather than complete incineration. Design improvements are required to achieve standard incineration temperatures.